Giant oscillations of the current in a dirty 2D electron system flowing perpendicular to a lateral barrier under magnetic field - Kadigrobov, A.M. (Физика низких температур, 2017)
The charge transport in a dirty 2-dimensional electron system biased in the presence of a lateral potential barrier under magnetic field is theoretically studied. The quantum tunnelling across the barrier provides the quantum interference of the edge states localized on its both sides that results in giant oscillations of the charge current flowing perpendicular to the lateral junction. Our theoretical analysis is in a good agreement with the experimental observations presented in Kang et al. [Lett. Nat. 403, 59 (2000)]. In particular, positions of the conductance maxima coincide with the Landau levels while the conductance itself is essentially suppressed even at the energies at which the resonant tunnelling occurs and hence these puzzling observations can be resolved without taking into account the electron-electron interaction.